IMPLEMENTATION OF VILLAGE INFORMATION SYSTEM (SID) AS A FORM OF VILLAGE GOVERNMENT DIGITAL GOVERNANCE - Muluk, Farid Anfasa; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to evaluate the implementation of the Village Information System (SID) as a form of digital governance in Sugihwaras Village, Candi Sub-district, Sidoarjo Regency. Method: Descriptive qualitative approach using semi-structured interviews with village officials (village head, village secretary, SID operator), direct observation of activities in the village office and SID website, and documentation study of village regulations, financial reports, and population data. Data analysis followed a cycle of reduction, presentation, and verification according to Miles & Huberman.   Results:  The results showed that the SID began operating in 2022 and has replaced manual processes with a website platform that provides modules on village profiles, news/announcements, self-service, documentation, and superior products. The implementation of SID improves administrative efficiency, budget transparency, and citizen participation, especially the younger generation, although community digital literacy and the quality of internet connections are still major obstacles. Support from the local government and village institutions plays an important role in the smooth implementation.   Novelty: The novelty of this study lies in the use of the New Public Management (NPM) framework to assess the integration of the principles of efficiency, transparency, accountability, and public orientation in the implementation of SID at the village level. In addition, this study maps the challenges of digital literacy and infrastructure in villages, and formulates applicable policy recommendations for sustainable information technology-based institutional capacity building.